Association of dietary patterns with serum high-sensitivity C-reactive protein level in community-dwelling older adults. (June 2019) - Chan, Ruth; Yu, Blanche; Leung, Jason; Lee, Jenny Shun-Wah; Woo, Jean
Summary: Introduction: Studies examining the association between dietary patterns and inflammatory markers are limited, in particular among Chinese older adults. Objective: We examined the association of various dietary patterns with serum high-sensitivity C-reactive protein (hsCRP) level in community-dwelling Chinese older adults, taking into account demographics and other lifestyle factors. Methods: We conducted ordinal regression analyses using baseline data based on 1332 older men and 1314 older women of Chinese origin from a cohort study of bone health in Hong Kong. Baseline interviewer administered questionnaires included dietary intake estimation and dietary pattern generation from the food frequency questionnaire, as well as demographic and lifestyle factors. Serum hsCRP was measured using a commercially available enzyme-linked immunosorbent assay. Results: In men, higher serum hsCRP level was associated with lower Diet Quality Index-International (DQI-I) score, the Mediterranean-DASH Intervention for Neurodegenerative Delay diet (MIND) score, Okinawan diet score, "vegetables-fruits" pattern score, and lower adherence to the Mediterranean diet. In women, serum hsCRP level was not associated with any dietary patterns. Conclusion: Our cross-sectional analyses suggest that various dietary patterns were associated with a lower serum hsCRP level in community-dwelling Chinese older adults, and these associations were only observed in older men.